Modern tools and current trends in web-development - Debani Prasad Mishra; Kshirod Kumar Rout; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2021)
In this paper, a social media platform like LinkedIn and Facebook is made using MongoDB as a database. This paper aims to touch all the modern tools required to make an efficient web app, keeping in mind both the customer satisfaction and the ease for the developers to make their web designs, front-end and back-end. In this application, a user could make an account, add or delete details of their profile, education, and experience fields. The users could post, also comment and even like a post of other users. A monolithic architectural approach is used for simplicity in maintaining the database. Postman application programming interface (API) was used to check the working of the back-end. Git, Github, and Heroku were used to deploy the website. Node package manager (NPM) packages like bcrypt and validator are used to encrypt passwords and to validate a user during login. Media queries are used in cascading style sheets (CSS) to achieve a responsive design. Therefore, the users could view the website through a mobile phone, i-pad and also a personal computer (PC), maintaining the readability and design across all these devices.